Land-use changes: methodological approach to understand the interactions nature / society in coastal areas - Lourenço, Nelson (2012)
The importance of Global Change research and Land-Use and Land-Cover Change (LUCC) studies reflects concerns about the need to understand the influence of human activities on the biogeochemical foundation of the biosphere as well as their impacts on climate change. Nowadays, since 1995, it is assumed the importance of LUCC as a substantial agent of change with great significance in climate change, loss of biodiversity, use of natural resources, human health and quality of life. Therefore we must perceive the influences of land-use and land-cover changes as a significant driving-force for Global Change.